Mechanistic analysis of endothelial lipase G promotion of the occurrence and development of cervical carcinoma by activating the phosphatidylinositol-4,5-bisphosphate 3-kinase/protein kinase B/mechanistic target of rapamycin kinase signalling pathway - Jing Huang; Renci Liu; Yiwen Zhang; Xiujie Sheng (Taylor & Francis Group, 2023)
Lipase G, endothelial type (LIPG) is expressed abundantly in tissues with a high metabolic rate and vascularisation. Research on LIPG has focussed on metabolic syndromes. However, the role of LIPG in providing lipid precursors suggests that it might function in the metabolism of carcinoma cells. Analysis in The Cancer Genome Atlas indicated that patients with cervical carcinoma with high LIPG expression had a lower survival prognosis compared with patients with low LIPG expression. The mechanism underlying the effects of LIPG in cervical carcinoma is unclear. The present study aimed to determine the role of LIPG in cervical carcinoma and its mechanism. The results showed that the LIPG expression level was higher in cervical cancer. Downregulation of LIPG expression inhibited cell migration, invasion, proliferation, and the formation of cell colonies, but increased the rate of apoptosis. The Human papillomavirus E6 protein might reduce the expression of miR-148a-3p, relieve the inhibitory effect of miR-148a-3p on LIPG expression, and promote the progression of cervical cancer through the phosphatidylinositol-4,5-bisphosphate 3-kinase/protein kinase B/mechanistic target of rapamycin kinase signalling pathway.IMPACT STATEMENT What is already known on this subject? LIPG provides lipid precursors, suggesting that it might function in the metabolism of carcinoma cells What do the results of this study add? LIPG might be regulated by HPV16 E6/miR-148a-3p and promote cervical carcinoma progression via the PI3K/AKT/mTOR signalling pathway. What are the implications of these finding for clinical practice and/or further research? The results indicated that novel treatment and diagnosis strategies for cervical carcinoma could be developed related to LIPG. However, the detailed relationship between LIPG and cervical carcinoma remains to be fully determined.